Efficacy of Florfenicol and Oxytetracycline Administered in Feed to Control Cisco Mortality Associated with Aeromonas salmonicida Infections. (3rd March 2023) - Cupp, Aaron R.; Tuttle‐Lau, Maren T.; Leis, Eric; Wolfe, Samantha L.; Smerud, Justin R.; Oliver, John W.; Erickson, Richard A.; Hannah, Austin P.; Johnson, Aaron E.; Nelson, Rachel G.; Standish, Isaac; Wils, Joel M.; et al.
Abstract: Two medications (one with florfenicol and one with oxytetracycline) that are approved in the United States to control mortality due to furunculosis associated with Aeromonas salmonicida were assessed to determine their efficacy in medicated feeds to treat A. salmonicida ‐infected Cisco (also known as Lake Herring) Coregonus artedi . Cisco were subjected to static infection baths containing A. salmonicida or a sham control and then were distributed to replicate test tanks within four treatment groups: (1) fish infected with A. salmonicida and treated with 15 mg florfenicol·kg body weight (BW) −1 ·d −1, (2) fish infected with A. salmonicida and treated with 83 mg oxytetracycline·kg BW −1 ·d −1, (3) fish infected with A. salmonicida and treated with a nonmedicated control feed, and (4) uninfected fish treated with a nonmedicated control feed. Medicated and comparative nonmedicated feed rations were administered at 2% BW/d for 10 consecutive days in accordance with the U.S. Food and Drug Administration‐approved drug label, followed by a 7‐d postdosing observation period using only nonmedicated feed. Cisco that were infected with A. salmonicida and treated with florfenicol (79% survival) and oxytetracycline (85% survival) had significantly higher survival than A. salmonicida ‐infected fish that received no medicated treatment (3% survival). No statistical difference in Cisco survival between the two medicated feed types was found. Aeromonas salmonicida was not detected in the kidney tissue of any surviving fish treated with medicated feeds at 7 d postdosing using quantitative PCR analysis. Overall, this study demonstrated that florfenicol‐ and oxytetracycline‐medicated feeds were effective A. salmonicida treatments for Cisco. Outcomes may inform ongoing propagation efforts for Cisco restoration within the Great Lakes basin.